PENGARUH BRAND EXPERIENCE, FITUR, KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA PENGGUNA APLIKASI GRAB DI KOTA BENGKULU - Restu, Muhammad; Hidayati, Arifah; Safrianti, Sintia (Politeknik Negeri Jakarta, 2023)
study aims determine effect of brandexperience, features and servicequality on consumer satis factionin Grabapplication users inBengkulu City. quantitative descriptiveresearch. The population this study usersGrab application inthe city ofBengkulu with sample sizeof 150 respondents using non-probability samplingtechnique. The analysis used SPSSversion 25. The results showed that (1) BrandExperience had a significanteffect on ConsumerSatisfaction using the GrabApplication inBengkulu City (2) Ease had a significant effect Consumer Satisfaction the GrabApplication inBengkulu City (3) ) ServiceQuality has a significant effect ConsumerSatisfaction the Application on Grab inbengkulu City (4) The Effect of BrandExperience, Features, ServiceQuality, significant effect on ConsumerSatisfaction the ApplicationGrab inBengkulu City.